Analysis of Trends and Phenomena of Motor Vehicle Tax Revenue in Kendal Regency (2017-2021) - Farah Rahmah Liya; Juliati; Nur Chayati; Saktiana Rizki Endiramurti (AKUMULASI: Indonesian Journal of Applied Accounting and Finance, 2022)
This study aims to analyze the trends and phenomena that occur in Motor Vehicle Tax (MVT) revenue in Kendal Regency. This study applies a descriptive, qualitative method. The results of the research have shown that MVT acceptance tends to fluctuate. The increase in MVT revenue is attributed to the success of the Kendal Regency Regional Revenue Management Unit (Unit Pengelolaan Pendapatan Daerah/UPPD) in carrying out its policy and service strategies. Meanwhile, the decline is due to an increase in open unemployment, the Work from Home (WFH) policy, a reduction in service hours, delays in offline outreach, the non-operation of several UPPD services, and a lack of community participation in responding to the MVT relief program.